A novel heterometallic platinum(ii)–silver(i) alkynyl complex [PtAg(dppm)2(CCC6H4COOCH3-4)2Cl] with two crystal morphologies exhibiting morphology-dependent photoluminescence. (26th September 2022) - Wei, Qiao-Hua; Zhang, Si-Qi; Ma, Xian-Jian; Huang, Zheng-Zhao; Wang, Bin
Abstract : A novel complex [PtAg(dppm)2 (CCC6 H4 COOCH3 -4)2 Cl] with two crystal morphologies as rod-like and prism was separately obtained by manipulating the recrystallization solvents. They exhibit glamorous morphology-dependent photoluminescence. Abstract : A novel heterometallic platinum(ii )–silver(i ) alkynyl complex [PtAg(dppm)2 (CCC6 H4 COOCH3 -4)2 Cl] (1 ) (dppm = bis(diphenylphosphino)methane) forms two different crystalline polymorphs that can be separately obtained on manipulating the recrystallization solvents. Two crystalline structures were confirmed by X-ray crystallography. Morphology-dependent photoluminescence behaviours were observed. Pale yellow rod-like crystals 1·CH2 Cl2 (1a ) exhibit strongly cyan luminescence ( λ em = 476 nm, τ = 10.8 μs) at room temperature and have a rhombohedral Pbca structure, while weak green luminescent prismatic crystals 1·2CH3 OH (1b ) ( λ em = 491 nm, τ = 3.3 μs) have a triclinic P 1̄ structure with shorter Pt⋯Ag distance (3.0418(3) Å), and significant intra/inter-molecular hydrogen bonds between O–H protons from different methanol molecules as H donors and an oxygen atom of the alkynyl ligand ( d O–H⋯O = 2.185 Å) from the 1 unit, and the Cl atom from the neighbouring 1 unit ( d O–H⋯Cl = 2.335 Å). Meanwhile, 1a displays significant mechanochromism, with an intriguing emission color change from cyan to green under UV irradiation at 365 nm. The powder XRD test results indicate that the morphology transition between crystalline and partial amorphous states is responsible for the mechanochromism phenomenon of 1a .